Production of (Z)-11-(heptanoyloxy)undec-9-enoic acid from ricinoleic acid by utilizing crude glycerol as sole carbon source in engineered Escherichia coli expressing BVMO-ADH-FadL - Sudheer, Pamidimarri D.V.N.; Seo, Dahee; Kim, Eun Joo; Chauhan, Sushma; Chunawala, J. R.; Choi, Kwon Young (Enzyme and Microbial Technology, 2018)
Production of (Z)-11-(heptanoyloxy)undec-9-enoic acid from recinoleic acid was achieved by whole-cell biotransformation by Escherichia coli, utilizing crude glycerol as the sole carbon source. Whole-cell biotransformation resulted in ∼93% conversion of the substrate ricinoleic acid to (Z)-11-(heptanoyloxy)undec-9-enoic acid. We replaced the inducer-dependent promoter system (T7 and Rhm promotors) with a constitutive promoter system. This resulted in successful expression of ADH, FadL, and E6-BVMO, without costly inducer addition. Efficacy evaluation of the whole-cell biotransformation by inducer-free system by five different E. coli strains revealed that the highest product titer was accumulated in E. coli BW25113 strain. The engineered inducer-free system using crude glycerol as the sole carbon source showed competitive performance with induction systems. Optimized conditions resulted in the accumulation of 7.38 ± 0.42 mM (Z)-11-(heptanoyloxy)undec-9-enoic acid, and when 10 mM substrate was used as feed concentration, the product titer reached 2.35 g/L. The inducer-free construct with constitutive promoter system that this study established, which utilizes the waste by-product crude glycerol, will pave the way for the economic synthesis of many industrially important chemicals, like (Z)-11-(heptanoyloxy)undec-9-enoic acid.
Keywords: BVMO; Constitutive promoters; Crude glycerol; Inducer-free expression; Ricinoleic acid; Bacterial Outer Membrane Proteins; Biotransformation; Carbon; Escherichia coli; Escherichia coli Proteins; Genetic Engineering; Glycerol; Ricinoleic Acids; Undecylenic Acids; (Z)-11-(heptanoyloxy)undec-9-enoic acid; BVMO; Constitutive promoter; Crude glycerol; Inducer-free expression; Ricinoleic acid